2010
DOI: 10.1021/np100325q
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial Triterpenoids from the Fruits of Neem, Azadirachta indica

Abstract: Eight known and two new triterpenoid derivatives, neemfruitins A (9) and B (10), have been isolated from the fruits of neem, Azadirachta indica, a traditional antimalarial plant used by Asian and African populations. In vitro antiplasmodial tests evidenced a significant activity of the known gedunin and azadirone and the new neemfruitin A and provided useful information about the structure-antimalarial activity relationships in the limonoid class.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 26 publications
7
58
0
Order By: Relevance
“…The tetranortriterpene has been shown to exhibit antifeedant activity against Mexican bean beetles, Epilachna varivestis (27,32). The limonoid has also been shown to possess antimalarial activity in in vitro antiplasmodial tests (33). In another study, the limonoid was shown to possess potent anticancer activity against breast cancer, melanoma, and prostate cancer cell lines (34).…”
Section: Although Tumor Necrosis Factor-related Apoptosis-inducing LImentioning
confidence: 99%
“…The tetranortriterpene has been shown to exhibit antifeedant activity against Mexican bean beetles, Epilachna varivestis (27,32). The limonoid has also been shown to possess antimalarial activity in in vitro antiplasmodial tests (33). In another study, the limonoid was shown to possess potent anticancer activity against breast cancer, melanoma, and prostate cancer cell lines (34).…”
Section: Although Tumor Necrosis Factor-related Apoptosis-inducing LImentioning
confidence: 99%
“…[2][3][4] During the past four decades, more than 200 compounds, including terpenoids, 1 flavones, 5 steroids, 6 coumarins 7 and polysaccharides 8 had been isolated from different parts of A. indica, and some of them showed the significant bioactivities such as insecticides, 1,9,10 antifungal, 1,3 antitumor 1,2,11,12 and antimalarial. 1,13,14 Azadirachtin, as a well known natural pesticide, 3,15 was always extracted from the kernels of A. indica. However, we recently noticed that the kernals after extracting azadirachtin were always disposed as waste without good use.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their high activities and reasonable availability, we choose representatives of the most important terpenic acids: from lupane group, we used betulinic acid (3) and dihydrobetulinic acid (4); from oleanane group, we used oleanolic acid (5) and morolic acid (6); from ursane group we used ursolic acid (7); from taraxastane group, we used heterobetulinic acid (8). In addition, we used non-acid terpenes such as oxoalloheterobetulon 15 and allobetulon 16.…”
Section: Resultsmentioning
confidence: 99%
“…These derivatives were shown to have many biological activities such as anticancer [2], antiviral [3], antifungal [4], antimalarial [5], antifeedant [6] and many others [7]. In our research group, we pay most attention to cytotoxic active derivatives of triterpenes.…”
Section: Introductionmentioning
confidence: 99%